Meningkatkan Kemampuan Berfikir Kritis Peserta Didik Menggunakan Model Problem Based Learning (PBL) dalam Pembelajaran Pendidikan Agama Katolik Kelas Viii Materi “Yesus Mewartakan Kerajaan Allah” di SMP Negeri 6 Surakarta Tahun Ajaran 2024-2025 - Daniel Fisher Polikarpus; Yusmanto Yusmanto; Busri Busri (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The aim of this study is to determine: 1) Whether the Problem-Based Learning (PBL) model can improve critical thinking skills, and 2) How to implement the PBL model effectively to enhance students' critical thinking. The PBL model guides students to think critically by utilizing interactive learning media such as educational videos and Lembar Kerja Peserta Didik (LKPD). These tools stimulate students' cognitive processes. This study used Penelitan Tindakan Kelas (PTK) with data collection techniques including observation, tests, non-tests, LKPD, and documentation. The research was conducted over two cycles, each consisting of the following stages: 1) Planning; 2) Implementation; 3) Observation; and 4) Reflection. The improvement in students' critical thinking was demonstrated by the average observation score of 73.8% in the first cycle, which increased to 83.8% in the second cycle. Based on the results, it can be concluded that the study showed a significant improvement in students' critical thinking skills, as evidenced by their enhanced ability to analyze questions, provide opinions, draw conclusions, and evaluate with the support of interactive and appropriate learning media.